Happiness - Kondor, Robbie (<<The>> Criterion Collection, 2024)
"As disturbingly funny as it is audaciously empathetic, auteur of unease Todd Solondz’s portrait of damaged souls reaching out for connection reveals the existential void underneath middle-class suburban "normalcy." An extraordinary ensemble cast—including Philip Seymour Hoffman, Jane Adams, Lara Flynn Boyle, Ben Gazzara, and Dylan Baker—embodies an array of loosely connected New Jersey deviants, depressives, and misfits, among them a frustrated phone-sex pest, an all-American dad concealing his pedophilic urges, and a lonely woman with a grisly secret, all of whom want just one thing: to be loved. One of the most controversial films of the 1990s, the unflinching Happiness unnerves precisely because it dares to see the humanity in those most often denied it." [criterion.com]
Original: USA 1998
Director-approved Blu-ray special edition features: new 4K digital restoration, supervised by director of photography Maryse Alberti, with 2.0 surround DTS-HD Master Audio soundtrack ; new conversation between director Todd Solondz and filmmaker Charlotte Wells ; new interview with actor Dylan Baker ; trailer ; English subtitles for the deaf and hard of hearing ; plus: An essay by screenwriter and novelist Bruce Wagner
Keywords: Film; Blu-Ray-Disc